The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fvets.2020.541747
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Renal Blood Flow Using Maximum Slope-Based Computed Tomography Perfusion and Ultrasound Flow Probe in Healthy Dogs

Abstract: Computed tomography (CT) perfusion can analyze tissue perfusion and quantitative parameters, including blood flow, blood volume, and transit time. CT perfusion has been used for evaluating split renal function. However, its applicability in veterinary medicine was not validated. This study aimed to evaluate the correlation of renal blood flow (RBF) derived by maximum slope-based CT perfusion and an ultrasonic flow probe and assess the effect of the presence of a pre-existing contrast medium on CT perfusion in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…A nonionic iodinated contrast medium (Omnipaque, GE healthcare, 350 mg I/mL, 350 mg I/kg) was administered through an intravenous catheter using a power injector according to the different conditions mentioned earlier. 18 To prevent stagnation of the contrast medium in the cerebral blood vessels, a 5-minute interval was allowed between injections across all injection rates. 22 The same procedure was repeated in the second experiment using a 20-gauge catheter.…”
Section: Brain Pctmentioning
confidence: 99%
See 1 more Smart Citation
“…A nonionic iodinated contrast medium (Omnipaque, GE healthcare, 350 mg I/mL, 350 mg I/kg) was administered through an intravenous catheter using a power injector according to the different conditions mentioned earlier. 18 To prevent stagnation of the contrast medium in the cerebral blood vessels, a 5-minute interval was allowed between injections across all injection rates. 22 The same procedure was repeated in the second experiment using a 20-gauge catheter.…”
Section: Brain Pctmentioning
confidence: 99%
“…14,15 In veterinary medicine, PCT has been used in disease diagnoses that require perfusion evaluation. Several studies on variables affecting PCT have been conducted in abdominal organs such as the liver, 16 kidney, 17,18 , and pancreas. 19 In addition, studies on the diagnosis of cerebrovascular diseases that require perfusion evaluation, such as degenerative diseases 20 and brain tumors 21 have been performed.…”
mentioning
confidence: 99%
“…Dynamic contrast‐enhanced computed tomography has been used in dogs, and several proof‐of‐principle studies have assessed normal tissues and tumors, and compared DCECT to 18F‐fluorodeoxyglucose positron emission tomography‐computed tomography. 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 Two studies specifically reported DCECT in nasal tumors but did not find correlation with histogenesis or survival. 33 , 39 Our objectives were (a) to assess baseline perfusion parameters in dogs with nasal tumors based on histopathological type, (b) to characterize changes in perfusion parameters with changes in tumor volume after the start of RT, and (c) to evaluate if a correlation existed of either objective 1 or objective 2 with survival.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic contrast‐enhanced computed tomography has been used in dogs, and several proof‐of‐principle studies have assessed normal tissues and tumors, and compared DCECT to 18F‐fluorodeoxyglucose positron emission tomography‐computed tomography 26‐42 . Two studies specifically reported DCECT in nasal tumors but did not find correlation with histogenesis or survival 33,39 .…”
Section: Introductionmentioning
confidence: 99%